The role of social media in creating brand awareness and purchase intention - Kurniasih, Dedeh; Alam, Surya; Bahrudin, Udin (Institute of Computer Science (IOCS), 2025)
Social media has become an integral part of modern marketing strategies, offering a powerful platform for businesses to connect with their target audience. The rise of social media platforms has revolutionized the way companies interact with consumers, which has a significant impact on brand awareness and purchase intent. The purpose of this study is to test and analyze the role of social media in creating brand awareness and purchase intention. The research method used is a SEM-PLS-based causality approach. The sample used was Nako Coffee consumers with a total of 100 respondents using the Lameshow formula. The results of this study provide an explanation that social media has a strong influence on brand awareness and purchase intention, and at the same time brand awareness can be a mediator in social media on purchase intention.